The authority relationship of Central and Local Governments in forming laws and regulations: between Indonesia and Malaysia - Aan Eko Widiarto; Muhamad Sayuti Hassan; Mohd Hazmi Mohd Rusli; Endrianto Bayu Setiawan (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study examines how the powers of the federal government and local governments interact to create laws and regulations in Malaysia and Indonesia. In most countries, the central government is not the only regulator in developing laws and regulations. Regional governments are vested with the authority to manage government affairs delegated to them. This authority includes the power to draft and enact regional regulations, reflecting regional independence in administering local governance. Regional regulations serve as strategic tools to achieve the objectives of decentralization, fostering greater autonomy by empowering regions to address local needs through tailored legislation. However, the delegation of such authority also presents the potential for regulatory conflicts between the central government and regional governments or among regions themselves. Consequently, a comprehensive analysis is essential to evaluate how the relationship between central and regional governmental authorities influences the legislative process in Indonesia. Employing a legal comparative approach provides an effective method for examining the dynamics of regulatory authority between the central and regional governments, offering valuable insights and policy recommendations to harmonize the framework for statutory regulation. The findings highlight those regional regulations play a crucial role in supporting decentralization, yet conflicts between central and regional authorities are inevitable. Comparing the cases of Indonesia and Malaysia, the study underscores the need for clear and collaborative frameworks to harmonize central and local authorities in forming laws and regulations, ensuring legal certainty and effective governance.